57 Association Between Secretory Phospholipase A2 Subtype v (PLA2G5) Genotype and Acute Respiratory Distress Syndrome in Infants. (October 2012) - Luca, D De; Minucci, A; Gentile, L; Piastra, M; Antonelli, M; Conti, G; Capoluongo, ED
Abstract : Background: Secretory Phospholipase A2 (PLA2) has been linked with acute respiratory distress syndrome (ARDS) and its clinical severity and mortality. The enzyme subtype -V (PLA2G5) is expressed in the lung tissue. We aimed at sequencing its gene (HGNC:9038) in infants with ARDS. This study is a part of a multicentre project whose protocol has been published elsewhere.[1] Methods: 24 ARDS and 24 age-matched babies with no lung disease were enrolled. 50 healthy adult volunteers, who never had neither ARDS nor chronic pulmonary diseases, served as another control group. Genomic DNA was extracted from leukocytes, amplified by PCR and sequenced, analyzing the coding regions by SeqScape. Basic clinical data were recorded. Results: A polymorphism (p.G3G=c.9C>T) was detected in the gene PLA2G5 (exon 1). This variation was present in heterozygosis in 42% of controls and in 17% of patients, while homozygosis was detected in 21% of patients and in no controls ( p =0.022). Heterozygosis and homozygosis were present in 54% and 10% of adult controls, respectively. Homozygosis for such polymorphism led to an increased risk of ARDS (OR: 6.7; 95% C.I.: [1.3–34.2]). Patients carrying this polymorphism had lower PaO2 /FiO2 ratio (104±29 vs 147±53; p =0.039) and higher lung injury score at the diagnosis (3.7±0.2vs3.2±0.4; p =0.031). Discussion: These are the first findings about genetic association between PLA2 and ARDS. Variation in the PLA2G5 gene might be associated to an increased risk for ARDS as it may represent a marker of variations in other genes nearby PLA2G5, that may be involved in inflammation pathway. [1] De Luca D, Capoluongo E, Rigo V & Study group on Secretory Phospholipase in Paediatrics. BMC Pediatr 2011; 11:101.